Application of Acoustic Radiation Force Impulse (ARFI) Elastography in Imaging of Delayed Onset Muscle Soreness (DOMS): A Comparative Analysis With 3T MRI - Hotfiel, Thilo; Kellermann, Marion; Swoboda, Bernd; Wildner, Dane; Golditz, Tobias; Grim, Casper; Raithel, Martin; Uder, Michael; Heiß, Rafael (Journal of Sport Rehabilitation, 2017)
DOMS is one of the most common reasons for impaired muscle performance in sports and is associated with reduced muscle strength and frequently observed both in professional and recreational athletes.To emphasize the diagnostic value of Acoustic Radiation Force Impulse (ARFI) in imaging of Delayed Onset Muscle Soreness by comparing findings to high-resolution 3T MRI T2 weighted sequences.Case series.Laboratory environment.Fifteen healthy students (7 female, 8 male, age 24 ± 4 years, height 178 ± 10 cm, body weight 67 ± 12 kg).ARFI values, represented as shear wave velocities (SWV) of the gastrocnemius muscle (GM) and soleus muscle (SM), as well as conventional ultrasound, high-resolution 3T MRI, creatine kinase activity, extension range of the ankle joint, calf circumference and muscle soreness were assessed before (baseline) and 60 hours after (post-intervention, PI) a standardized eccentric exercise.ARFI SWV values of the GM revealed a statistically significant decrease of 19.1% between baseline (2.2 ± 0.26 m/s) and PI (1.78 ± 0.24 m/s); p=0.008. At follow-up, the MRI investigations showed intramuscular oedema for the GM in all participants corresponding to a significant raise in T2 signal intensity (p=0.001) and in T2-time values (p=0.004).ARFI elastography seems to be an additional sensitive diagnostic modality in the diagnostic work up of DOMS. Intramuscular SWV could represent an additional imaging marker for the assessment and monitoring of ultrastructural muscle injuries and therefore be helpful for individual training composition in elite sports.
EVALuna2:10902

Automatic detection of foreign objects and contaminants in colonoscopic video data using deep learning - Kress, Veronika; Wittenberg, Thomas; Raithel, Martin; Bruns, Volker; Lehmann, Edgar; Eixelberger, Thomas; Hackner, Ralf (Current Directions in Biomedical Engineering, 2022)
Introduction: In the field of colonoscopy results of automated or supporting procedures using medical image processing are often compromised by contaminants such as blood or stool, but also due to medical instruments. Such objects or contaminations often obscure relevant areas or cause disturbances in various algorithms and also prevent physicians from recognizing relevant information in the video-stream. Hence, automatic detection and segmentation of such contaminations is desirable, by obtaining proper segmentation masks to an algorithm yields the possibility to exclude such areas from analysis. Method: We created a training and validation dataset by collecting (and annotating, where necessary) endoscopic video sequences from various public available datasets and a privat collection. An encoder-decoder deep convolutional neural network was trained with this data to predict segmentation masks for blood, stool, medical instruments and other objects. Results: Depending on the class (blood, stool, ...), we were able to obtain a mean Dice score in the range between 0.88 to 0.93 on the evaluation dataset. Conclusion: The proposed approach hence allows us providing segmentation masks that are able to reduce problems in the subsequent image analysis and also find regions that were not properly observed.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Blood; Colonoscopy; Deep learning; Instrument; Object detection; Segmentations; Stool

Biological Therapy of NSAID Intolerance and Food Allergy with Eggs of Pig WhipwormTrichiuris suis (TSO) in combination with Antiallergic Drugs - Heinrich, Johanna; Hotfiel, Katharina; Rieker, Ralf; Finzel, Stefanie; Goj, Detlef; Raithel, Martin (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Confocal laser endomicroscopy for the in vivo detection of intraepithelial neoplasia in PeutzJeghers polyps - Neumann, Helmut; Vieth, Michael; Raithel, Martin; Mudter, Jonas; Kiesslich, R.; Neurath, Markus (Endoscopy, 2010)
CRIS-Team Scopus Importer:2025-03-05

Deep-learning based reconstruction of the stomach from monoscopic video data - Hackner, Ralf; Raithel, Martin; Lehmann, Edgar; Wittenberg, Thomas (Current Directions in Biomedical Engineering, 2020)
For the gastroscopic examination of the stomach, the restricted field of view related to the „keyhole“-perspective of the endoscope is known to be a visual limitation. Thus, a panoramic extension can enlarge the field of vision, supports the endoscopist during the examination, and ensures that all of the inner stomach walls are visually inspected. To compute such a panorama of the stomach, knowledge about the geom-etry of the underlying structure is required. Structure from mo-tion an approach to reconstruct the necessary information about the 3D-structure from monocular image sequences as provided by a gastroscope. We examine and evaluate an exist-ing deep neuronal network for stereo reconstruction, in order to approximate the geometry of stomach parts from a set of consecutive acquired image pairs from gastroscopic video
Keywords: Endoscopy; 3D-reconstruction; deep neural networks; panoramic imaging.

Detection of Local Intestinal IgE Antibodies to Foods in Irritable Bowel Syndrome and Effect of an Antigen-Specific Diet on Irritable Bowel Syndrome (IBS) Type, Severity, and Symptoms - Raithel, Martin; Krischke, Eugenia; Kressel, Juergen; Krischke, Frederick; Albrecht, Heinz; Hotfiel, Katharina; Schultis, Wolfgang; Hagel, Alexander (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Double-balloon-enteroscopy-based endoscopic retrograde cholangiopancreatography in post-surgical patients - Raithel, Martin; Dormann, Harald; Naegel, Andreas; Boxberger, Frank; Hahn, Eckhart; Neurath, Markus; Maiß, Jürgen (World Journal of Gastroenterology, 2011)
AIM: To evaluate double balloon enteroscopy (DBE) in post-surgical patients to perform endoscopic retrograde cholangiopancreatography (ERCP) and interventions. METHODS: In 37 post-surgical patients, a stepwise approach was performed to reach normal papilla or enteral anastomoses of the biliary tract/pancreas. When conventional endoscopy failed, DBE-based ERCP was performed and standard parameters for DBE, ERCP RESULTS: Push-enteroscopy (overall, 16 procedures) reached enteral anastomoses only in six out of 37 post-surgical patients (16.2%). DBE achieved a high rate of luminal access to the biliary tract in 23 of the remaining 31 patients (74.1%) and to the pancreatic duct (three patients). Among all DBE-based ERCPs (86 procedures), 21/23 patients (91.3%) were successfully treated. Interventions included ostium incision or papillotomy in 6/23 (26%) and 7/23 patients (30.4%), respectively. Biliary endoprosthesis insertion and regular exchange was achieved in 17/23 (73.9%) and 7/23 patients (30.4%), respectively. Furthermore, bile duct stone extraction as well as ostium and papillary dilation were performed in 5/23 (21.7%) and 3/23 patients (13.0%), respectively. Complications during DBE-based procedures were bleeding (1.1%), perforation (2.3%) and pancreatitis (2.3%), and minor complications occurred in up to 19.1%. CONCLUSION: The appropriate use of DBE yields a high rate of luminal access to papilla or enteral anastomoses in more than two-thirds of post-surgical patients, allowing important successful endoscopic therapeutic interventions. © 2011 Baishideng. All rights reserved.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Choledochojejunostomy; Double balloon enteroscopy; Endoscopic retrograde cholangiopancreatography; Hepaticojejunostomy; Pancreaticojejunostomy; Percutaneous cholangiodrainage

Endoscopic Submucosal Dissection in the distal Anorectum: Effectiveness, Safety and unexpected Side Effects, and the Need for comprehensive Patient Information - Raithel, Martin; Hagel, Alexander; Anneken, Andrea; Albrecht, Heinz; Vitali, Francesco; Bruetting, Alfred (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

First Presentation of idiopathic Mast Cell Activation Syndrome (MCAS) in a Young Person: Association with Histamine and Salicylate Intolerance as well as an important Differential Diagnosis in gastroenterological Problem Patients - Raithel, Martin; Rechenauer, Tobias; Goetze, Thomas; Siebenlist, Gregor; Rueckel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, Andre (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Gastrointestinale Erscheinungsformen der systemischen Mastzellaktivierungserkrankung – Eine praxisorientierte Einführung in Klinik, Diagnostik und Therapie - Raithel, Martin; Homann, Jürgen; Rieker, Ralf; Molderings, Gerhard J. (Zeitschrift für Gastroenterologie, 2025)
Systemic mast cell activation disease (MCAD) is an epigenetic and genetic disease entity with a very pronounced clinical symptomatology in a variety of clinical manifestations in potentially every organ and tissue due to inappropriate release of mast cell mediators accompanied with the accumulation of both morphologically normal and mutated mast cells. Due to the prevalence of the disease of 17% in Germany, gastroenterologists and endoscopists are often unknowingly faced with MCAD in everyday clinical practice. In addition, gastroenterological examinations are an essential part of the diagnosis of MCAD. It is therefore essential for every physician working in gastroenterology to possess basic knowledge of this disease and, in particular, to be informed about its problems in the field of gastroenterology. This overview summarizes the current state of knowledge on the causes, diagnosis and treatment of the highly complex MCAD, focusing on the gastroenterological aspects.
CRIS-Team Scopus Importer:2025-02-28

Idiopathic Mast Cell Activation Syndrome With Associated Salicylate Intolerance - Rechenauer, Tobias; Raithel, Martin; Goetze, Thomas; Siebenlist, Gregor; Rueckel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, Andre (Frontiers in Pediatrics, 2018)
Idiopathic mast cell activation syndrome can be a rare cause for chronic abdominal pain in children. It remains a diagnosis by exclusion that can be particularly challenging due to the vast variety of possible clinical manifestations. We present a 13-year-old boy who suffered from a multitude of unspecific complaints over a long period of time. In this case, an assessment of mast cell-derived metabolites and immunohistochemical analysis of bioptic specimen was worthwhile. After ruling out, primary (oncologic) and secondary causes for mast cell activation, pharmacologic treatment adapted to the patient's salicylate intolerance resulted in a major relief of symptoms.
EVALuna2:34101

Intravenous vitamin C in the treatment of allergies: an interim subgroup analysis of a long-term observational study - Vollbracht, Claudia; Raithel, Martin; Krick, Bianka; Kraft, Karin; Hagel, Alexander (Journal of International Medical Research, 2018)
Objective Oxidative stress appears to be a key factor in the pathogenesis of allergic diseases and a potential therapeutic target in allergy treatment. Allergic diseases are reportedly associated with reduced plasma levels of ascorbate, which is a key physiological antioxidant. Ascorbate prevents excessive inflammation without reducing the defensive capacity of the immune system. Methods An interim analysis of a multicenter, prospective, observational study was conducted to investigate the change in disease-specific and nonspecific symptoms (fatigue, sleep disorders, depression, and lack of mental concentration) during adjuvant treatment with intravenous vitamin C (Pascorbin®; Pascoe, Giessen, Germany) in 71 patients with allergy-related respiratory or cutaneous indications. Results Between the start and end of treatment, the mean sum score of three disease-specific symptoms decreased significantly by 4.71 points and that of four nonspecific symptoms decreased significantly by 4.84 points. More than 50% of patients took no other allergy-related medication besides vitamin C. Conclusions Our observations suggest that treatment with intravenous high-dose vitamin C reduces allergy-related symptoms. Our observations form a basis for planning a randomized controlled clinical trial to obtain more definitive evidence of the clinical relevance of our findings. We also obtained evidence of ascorbate deficiency in allergy-related diseases. TRIAL REGISTRATION: Clinical Trials NCT02422901.
EVALuna2:35145

Modern anticoagulation with factor Xa inhibitors in oncology: is the gastrointestinal bleeding rate (also) decisive? - Raithel, Martin; Haibach, Martina; Kremenevski, Igor; Arnold, Erich; Ringwald, Jürgen (Zeitschrift für Gastroenterologie, 2022)
The increased risk of thrombosis and bleeding with an active tumor disease is known as the so-called "thrombo-hemorrhagic syndrome", which places high demands on anticoagulation. There are currently 4 randomized, prospective studies on the use of new, non-vitamin K dependent oral anticoagulants (NOAC) for the treatment of venous thromboembolism (VTE) that have occurred in oncology. The FXa inhibitors rivaroxaban, edoxaban and twice apixaban were each used in individual studies versus the standard therapeutic agent dalteparin. Since there is no direct head-to-head comparison of the FXa inhibitors mentioned within a study, the largest study - always compared to dalteparin - was evaluated for each NOAC. The studies were analyzed with regard to their effectiveness, safety, fatal bleeding rates, the risk of gastrointestinal bleeding (GIB) and other differences using descriptive statistics. With dalteparin, the mean VTE recurrence rate was approximately 9% over a 6-month treatment period. All three FXa inhibitors were not inferior to dalteparin in terms of potency. The VTE recurrence rate was - 2.3% lower in edoxaban and apixaban-treated patients and - 5.0% in rivaroxaban-treated patients. In terms of safety, there was an increased rate of severe bleeding (both + 2.4%) for rivaroxaban and edoxaban compared to dalteparin; in particular, the number of GIBs was significantly increased. In contrast, the number of severe bleeding was not increased for apixaban, as was the case for various bleeding types including GIB. In the Apixaban study, the overall rate of severe GIB, which accounted for about 50% of all severe bleeding, and that of clinically relevant non-severe bleeding, were the lowest. The FXa inhibitors are not inferior to the standard therapy with dalteparin in the VTE recurrence rate in oncological patients. The GIB rate appears to be an important predictive factor for the safety of this group of substances, so that tumor location, gastrointestinal risk factors and other individual criteria should be given greater consideration in future therapy decisions for or against an FXa inhibitor.
CRIS-Team WoS Importer:2022-08-05

Modern enteroscopic interventions and characterization of nonmalignant postsurgical biliary anastomosis by double-balloon endoscopy - Raithel, Martin; Naegel, A.; Dormann, Harald; Derossi, Th; Diebel, H.; Raithel, S.; Krauss, F.; Hahn, E. G.; Maiss, J. (Surgical Endoscopy, 2011)
Background: Endoscopic access to strictured biliodigestive anastomoses often is difficult and may require percutaneous transhepatic biliary drainage or reoperation. Methods: Push- or push-and-pull enteroscopy was used to diagnose disease and treat 24 postsurgical patients with suspected strictured biliodigestive anastomosis. Endoscopic retrograde cholangiography and biliary interventional procedures were used. Endoscopic accessibility, diagnosis of disease, therapeutic success, and complication rates were investigated at a single tertiary university gastroeneterology center. Results: Push enteroscopy reached biliary enteroanastomoses in 5 of the 24 patients (20.8%), whereas push-and-pull enteroscopy found choledocho- or hepaticojejunostomies in 17 of the remaining 19 postsurgical patients (89.4%). In all, successful enteroscopic intervention was achieved for 21 of the 24 patients (87.5%), whereas only 3 patients had to undergo percutaneous cholangiodrainage (12.5%). Cicatricially changed biliodigestive anastomoses were found in 14 of 21 patients (66.6%) including a mucosal type stricture in 7 patients (50%), an intramural type stricture in 5 patients (35.7%), and a ductal type stricture in 2 patients (14.2%). The remaining seven patients (33.3%) were normal. Enteroscopic interventions at strictured biliodigestive anastomosis included ostium incision for 8 (57.1%) and endoprosthesis insertion for 13 (92.8%) of the 14 patients, with prompt resolution of cholestasis and cholangitis. The major complications for the 24 patients involving 68 double-balloon enteroscopy (DBE) examinations comprised 2 perforations (8.3% per patient), 1 mild peritonitis (4.1%), and 1 cholangitis (4.1%), whereas minor complications were experienced by up to 20.8% of the patients. Conclusions: Modern interventional enteroscopy yields a high rate of successful interventions for strictured biliodigestive anastomosis, requires ostium incision for mucosal and intramural types of strictures, and helps to reduce percutaneous approaches. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Biliodigestive anastomosis; Endoscopic retrograde cholangiography; Push enteroscopy; Push-and-pull-enteroscopy

Mucosal Mast Cell Distribution in the Gastrointestinal Tract of Children: A Preliminary Study for Establishing Reference Values - Ehrsam, Christoph; Rechenauer, Tobias; Allabauer, Ida; Siebenlist, Gregor; Kaspar, Sonja; Rieger, Daniel; Schmid, Margit; Ruckel, Aline; Wölfle, Joachim; Hartmann, Arndt; Rieker, Ralf; Raithel, Martin; et al. (Journal of Pediatric Gastroenterology and Nutrition, 2022)
Objectives: The physiological number and distribution of mast cells (MCs) in the pediatric gastrointestinal (GI) tract is not well defined and reference values of normality are missing. To define a physiological and disease defining cut-off, a systematic histological exploration of MC distribution from the esophagus to the rectum in healthy as well as in patients with gastrointestinal food allergies (GFA) was performed. Methods: Nine pediatric subjects that exhibited unremarkable histopathological evaluations or underwent endoscopy for surveillance reasons after a previous polypectomy of single colonic juvenile polyps served as reference cohort. In all of these subjects, a chronic inflammatory disease (eg, inflammatory bowel disease, celiac disease) or allergy was excluded. In addition, a group of 15 patients with gastrointestinal complaints suspected to be caused by a GFA were investigated. Immunohistochemistry was performed from all biopsies using CD117 (c-Kit) as a reliable marker to identify MCs in the lamina propria. Results: There were distinct differences of MC counts in all parts of the pediatric GI tract. The highest counts of MCs in both symptomatic patients and control cohort, were found in the duodenum, terminal ileum, cecum and ascending colon. The lowest counts were found in the esophagus. Significant disparities between GFA and healthy subjects were found in the gastric corpus (22.1 +/- 4.0/ high power field [HPF] vs 32.0 +/- 10.1/HPF; P = 0.034) and ascending colon (44.8 +/- 10.4/HPF vs 60.4 +/- 24.3/HPF; P = 0.047). Conclusions: Mucosal MC counts in the pediatric GI tract are higher than previously reported, with a considerable overlap between healthy and GFA patients. These results provide detailed information on distribution and numbers of MCs in pediatric allergic patients while allowing estimates of physiological values in childhood for the first time. With regard to diagnostic procedures in GFA further laboratory parameters have to be integrated.
CRIS-Team WoS Importer:2022-01-07

Omalizumab Therapy for Bronchial Asthma (AB), NSAID Intolerance and Mast Cell Activation (MCAS) led to reproducible heavy vaginal Bleeding in a Patient with systemic Lupus erythematosus (SLE) and Endometriosis - Rossmeissl, Anja; Hotfiel, Katharina; Klimek, Ludger; Hildebrandt, Thomas; Kremenevskiy, Igor; Finzel, Stefanie; Dostmann, Lisa; Raithel, Martin (INTERNIST, 2020)
CRIS-Team WoS Importer:2020-05-05

Panendoscopic characterization of PeutzJeghers syndrome - Neumann, Helmut; Vieth, Michael; Mudter, Jonas; Raithel, Martin; Neurath, Markus (Endoscopy, 2010)
CRIS-Team Scopus Importer:2025-03-05

Panorama Mapping of the Esophagus from Gastroscopic Video - Prinzen, Martin; Raithel, Martin; Bergen, Tobias; Mühldorfer, Steffen; Nowack, Sebastian; Wilhelm, Dirk; Wittenberg, Thomas (Bildverarbeitung für die Medizin 2015, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD9.panora
Keywords: Endoscopy; Visualistaion; Esophagus

Panoramic Endoscopy of the Stomach: First results from Phantom and Patient Data. - Hackner, Ralf; Hann, Alexander; Franz, Daniela; Meining, Alexander; Raithel, Martin; Wittenberg, Thomas (Proc's 17. Jahrestagung der Deutschen Gesellschaft für Computer- und Roboterassistierte Chirurgie (CURAC 2018), 2018)
For gastroscopic examinations of the stomach, the limited field of vision related to the keyhole view of the endoscope can be a problem. A panoramic view of the gastroscopic images can enlarge the field of vision and may ensure that the performing physician has examined all of the stomach walls. Nevertheless, the complex geometry the stomach renders does not allow a straight forward stitching or mosaicking of a panorama. Therefore, for primary experiments in the field of panoramic endoscopy of the stomach we subdivided the stomach in four areas (fundus, antrum, lesser and greater curvature of the body of the stomach). We adapted methods for panoramic bladder-mosaicking in order to stitch endoscopic image-sequences from two different phantoms of the stomach and a real gastroscopic examination. With the obtained “panoramic map”, the physician can ensure that the entire stomach was examined, document and annotate findings and communicate these to other physicians.<br
Keywords: Endoscopy; Panorama; Stomach; Mosaicking; Stitching

The alternative serotonin transporter promoter P2 impacts gene function in females with irritable bowel syndrome - Mohr, Sandra; Fritz, Nikola; Hammer, Christian; Martínez, Cristina; Berens, Sabrina; Schmitteckert, Stefanie; Wahl, Verena; Schmidt, Malin; Houghton, Lesley A.; Goebel-Stengel, Miriam; Kabisch, Maria; Götze, Dorothea; et al. (Journal of Cellular and Molecular Medicine, 2021)
Irritable bowel syndrome (IBS) is a gut-brain disorder in which symptoms are shaped by serotonin acting centrally and peripherally. The serotonin transporter gene SLC6A4 has been implicated in IBS pathophysiology, but the underlying genetic mechanisms remain unclear. We sequenced the alternative P2 promoter driving intestinal SLC6A4 expression and identified single nucleotide polymorphisms (SNPs) that were associated with IBS in a discovery sample. Identified SNPs built different haplotypes, and the tagging SNP rs2020938 seems to associate with constipation-predominant IBS (IBS-C) in females. rs2020938 validation was performed in 1978 additional IBS patients and 6,038 controls from eight countries. Meta-analysis on data from 2,175 IBS patients and 6,128 controls confirmed the association with female IBS-C. Expression analyses revealed that the P2 promoter drives SLC6A4 expression primarily in the small intestine. Gene reporter assays showed a functional impact of SNPs in the P2 region. In silico analysis of the polymorphic promoter indicated differential expression regulation. Further follow-up revealed that the major allele of the tagging SNP rs2020938 correlates with differential SLC6A4 expression in the jejunum and with stool consistency, indicating functional relevance. Our data consolidate rs2020938 as a functional SNP associated with IBS-C risk in females, underlining the relevance of SLC6A4 in IBS pathogenesis.
CRIS-Team Scopus Importer:2021-07-02
Keywords: 5-HT; IBS; IBS-C; serotonin transporter

The Application of Hemospray in Gastrointestinal Bleeding during Emergency Endoscopy - Hagel, Alexander; Albrecht, Heinz; Naegel, Andreas; Vitali, Francesco; Vetter, Marcel; Dauth, Christine; Neurath, Markus; Raithel, Martin (Gastroenterology Research and Practice, 2017)
Introduction . Gastrointestinal bleeding represents the main indication for emergency endoscopy (EE). Lately, several hemostatic powders have been released to facilitate EE.Methods. We evaluated all EE in which Hemospray was used as primary or salvage therapy, with regard to short- and long-term hemostasis and complications.Results. We conducted 677 EE in 474 patients (488 examinations in 344 patients were upper GI endoscopies). Hemospray was applied during 35 examinations in 27 patients (19 males), 33 during upper and 2 during lower endoscopy. It was used after previous treatment in 21 examinations (60%) and in 14 (40%) as salvage therapy. Short-term success was reached in 34 of 35 applications (97.1%), while long-term success occurred in 23 applications (65.7%). Similar long-term results were found after primary application (64,3%) or salvage therapy (66,7%). Rebleeding was found in malignant and extended ulcers. One major adverse event (2.8%) occurred with gastric perforation after Hemospray application.Discussion. Hemospray achieved short-term hemostasis in virtually all cases. The long-term effect is mainly determined by the type of bleeding source, but not whether it was applied as first line or salvage therapy. But, even in the failures, patients had benefit from hemodynamic stabilization and consecutive interventions in optimized conditions.
EVALuna2:33829

The serotonin receptor 3E variant is a risk factor for female IBS-D - Fritz, Nikola; Berens, Sabrina; Dong, Yuanjun; Martínez, Cristina; Schmitteckert, Stefanie; Houghton, Lesley A.; Goebel-Stengel, Miriam; Wahl, Verena; Kabisch, Maria; Götze, Dorothea; D’Amato, Mauro; Zheng, Tenghao; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT3 receptor family. 5-HT3Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT3R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients (p = 0.0187); more specifically, in those diagnosed with IBS-D (p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Females; IBS-D; Irritable bowel syndrome; Serotonin type 3 receptor

Training and education of young physicians and engineers in the field of endoscopy and laparoscopy-a review of Germany-wide joint cooperation and training possibilities - Wichmann, Dörte; Duckwort-Mothes, Benedikt; Hirt, Bernhard; Wilhelm, Dirk; Steger, Jana; Zweimüller, Martin; Küllmer, Armin; Raithel, Martin; Maiss, Jürgen; Pott, Peter; Wittenberg, Thomas (Current Directions in Biomedical Engineering, 2023)
Introduction: Application-related (hands-on) training and instruction is an essential component in the advanced education of physicians in residency. To teach and train required endoscopic examinations and interventions in a standardized manner, courses are offered by various societies. Within these courses the assistant endoscopists learn and train how to use the technical equipment and how to perform the examinations and related interventions. Similarly, for graduate biomedical engineering students with a job-or research-related interest in the field of endoand laparoscopy, an early involvement and practical introduction to the instrumentation and techniques-if possible already during their studies-can generate a fundamental understanding of the technical requirements as well needs of the physicians. Objective: As various such (hands-on) training-courses for flexible and rigid endoscopy specifically addressing young physicians, surgeons as well as engineers are offered by numerous institutes, this contribution tries do provide a structured overview on/over these possibilities. Material: Known cross-institutional courses in the field of endo-and laparoscopy currently offered in Germany in cooperation of physicians and engineers are listed and briefly described. Results: A total of n = 4 crossinstitutional courses for the introduction and training in flexible and rigid endoscopy have been identified. Discussion: The cross-institutional courses for physicians and technicians in the field of endo-and laparoscopy presented serve to provide a better understanding of the subject matter and the field of either discipline. Questions that arise in the field of endoscopy from physicians can be addressed at an early stage and, if necessary, worked on with little effort. Ideas for new instruments and even new interventions can arise and be pursued through an intensive exchange between technicians and physicians. Collaborations are established on a local basis which will foster national activities in this field and which allow to develop competencies relevant for the industrial sector of medical engineering.
CRIS-Team Scopus Importer:2023-10-20
Keywords: education; Endoscopy; hands-on training; interdisciplinary cooperation; laparoscopy